Cognitive enhancement interventions for people with bipolar disorder: A systematic review of methodological quality, treatment approaches, and outcomes. (31st October 2019) - Tsapekos, Dimosthenis; Seccomandi, Benedetta; Mantingh, Tim; Cella, Matteo; Wykes, Til; Young, Allan H.
Abstract: Background: Patients with bipolar disorder (BD) suffer from cognitive deficits across several domains. The association between cognitive performance and psychosocial functioning has led to the emergence of cognition as a treatment target. Objective: This study reviews the existing literature on cognitive enhancement interventions for people with BD, focusing on different treatment approaches and methodological quality. Methods: We conducted a systematic search following the PRISMA guidelines. Sample characteristics and main outcomes for each study and treatment characteristics for each approach were extracted. Study quality was assessed using the Clinical Trials Assessment Measure (CTAM) and Cochrane Collaboration's Risk of Bias tool by independent raters. Results: Eleven articles reporting data from seven original studies were identified encompassing 471 participants. Two treatment approaches were identified, cognitive and functional remediation. For controlled studies, methodological quality was modest (average CTAM score = 60.3), while the overall risk of bias was considered moderate. Beneficial effects on cognitive or functional outcomes were reported in the majority of studies (91%), but these findings were isolated and not replicated across studies. Key methodological limitations included small sample sizes, poor description of randomization process, high attrition rates, and participant exclusion from the analysis. Conclusions: Findings are promising but preliminary. Quality studies were few and mostly underpowered. Heterogeneity in sample characteristics, outcome measures, and treatment approaches further limit the ability to generalize findings. Adequately powered trials are required to replicate initial findings, while moderators of treatment response and mechanisms of transfer need to be explored.